Glanzmann thrombasthenia: Multidisciplinary management A case report - Rivas, Gianmarco (2023)
Dental management of a patient with Glanzmann's thrombasthenia is complex. This disease is characterized by dysfunction of platelet aggregation due to the increased risk of bleeding during surgery. In this case report, a female patient was administered a factor VIIa-based drug that helps us control bleeding episodes that occur during dental treatment, based on a multidisciplinary approach with the hematology service and the surgery service. oral and maxillofacial of the Guillermo Almenara Irigoyen National Hospital.